Racism and Ethnic Inequality in a Time of Crisis Findings from the Evidence for Equality National Survey - Finney, Nissa; Nazroo, James; Bécares, Laia; Kapadia, Dharmi; Shlomo, Natalie (Policy Press, 2023)
ePUB and EPDF available Open Access under CC-BY-NC-ND licence. This book illustrates life through the COVID-19 pandemic for ethnic minorities in Britain. Drawing from the Evidence for Equality National Survey (EVENS), the book presents new evidence of ethnic inequalities and sheds new light on underlying racisms, opening them up to debate as crucial social concerns. Written by leading international experts in the field, this is a must-read for anyone interested in contemporary ethnic inequalities and racism from academics and policy makers to voluntary and community sector organisations.